False for every rate there is only one unit rate. there is however more than 1 rates for one unit rate. for example 4/2 would have 2/1 as a unit rate but 2/1 can have 4/2 and 8/4 as rates and so on. hope this helps good luck!
F(x) = 3x+1
G(x) = X^2 - 6
F(G(x)) = F(X^2 - 6) = 3(X^2 - 6) + 1 = 3X^2 - 18 + 1 = 3X^2 -17
F(G(x)) = 3X^2 - 17
I need the actual problem to answer this question
<u><em>Its Going to Be Table B! Good Luck :)⇔</em></u>
Step-by-step explanation:
![{x}^{2} - 14x - 25 {y}^{2} + 100y = 76](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%20-%2025%20%7By%7D%5E%7B2%7D%20%20%2B%20100y%20%3D%2076)
Factor by grouping,
![( {x}^{2} - 14x) - (25 {y}^{2} - 100y) = 76](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%29%20%20%20-%20%2825%20%7By%7D%5E%7B2%7D%20%20-%20100y%29%20%3D%2076)
Complete the square, with the x variables,
![( {x}^{2} - 14x + 49) - (25 {y}^{2} - 100y) = 125](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%2B%2049%29%20%20-%20%2825%20%7By%7D%5E%7B2%7D%20%20-%20100y%29%20%3D%20125)
Factor out 25 for the y variables
![( {x}^{2} - 14x + 49) - 25( {y}^{2} - 4y) = 125](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%2B%2049%29%20-%2025%28%20%7By%7D%5E%7B2%7D%20%20-%204y%29%20%3D%20125)
Complete the square
![( {x}^{2} - 14x + 49) - 25( {y}^{2} - 4y + 4) = 25](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%2B%2049%29%20-%2025%28%20%7By%7D%5E%7B2%7D%20%20-%204y%20%2B%204%29%20%3D%2025)
Simplify the perfect square trinomial
![(x - 7) {}^{2} - 25(y - 2) {}^{2} = 25](https://tex.z-dn.net/?f=%28x%20-%207%29%20%7B%7D%5E%7B2%7D%20%20-%2025%28y%20-%202%29%20%7B%7D%5E%7B2%7D%20%20%3D%2025)
Make the right side be 1 so divide everything by 25.
![\frac{(x - 7) {}^{2} }{25} - (y - 2) {}^{2} = 1](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28x%20-%207%29%20%7B%7D%5E%7B2%7D%20%7D%7B25%7D%20%20-%20%20%28y%20-%202%29%20%7B%7D%5E%7B2%7D%20%20%3D%201)
Here our center is (7,2).